Transformation Characteristics of Hydrogen-Donor Solvent Tetralin in the Process of Direct Coal Liquefaction - Chang, Hai-zhou; Li, Jun-qi; Du, Shuai; Shen, Kai-yuan; Yang, Qun; Yi, Han; Zhang, Ji-wei (Frontiers in Chemistry, 2019)
The aim of this study is to investigate the transformation of hydrogen-donor solvent tetralin in the direct liquefaction process of coal. Pure tetralin liquid as well as mixture of tetralin and Wucaiwan coal (WCW) were separately reacted under a liquefaction condition, and constituents of liquid product were analyzed by GC-MS. The results revealed that after the tetralin liquid reacted with high-pressure hydrogen, 90% of the reaction product was in liquid state, the gaseous products mainly included alkane gas and COx gas. When the reaction temperatures were set at 380°C and 420°C respectively, the corresponding transformation rates of tetralin can be 34.72% and 52.74%. At 380°C, the tetralin mainly plays a role of passing active hydrogen, while at 420°C, it mainly occurs dehydrogenation transformation to provide active hydrogen, as well as generate naphthalene, methyl indan and substituted benzene, etc. Taking tetralin as the hydrogen-donor solvent, the WCW was performed liquefaction reaction, and the obtained results showed that the transformation rates of tetralin were 69.76% and 83.86% at liquefaction temperatures of 380°C and 420°C, respectively. Tetralin mainly occurs dehydrogenation transformation to generate naphthalene, followed by methyl indan, where contents order of main constituents of the liquefaction products were: naphthalene> tetralin > methyl indan.